Tata Kelola (Governance) Kopi Arabika Spesial Dalam Rantai Nilai (Jurnal Agribisnis Indonesia, 2025)
The development of the third wave coffee culture has increased consumer demand for specialty coffee. Arabica coffee is known as specialty coffee because of its unique taste and quality. Specialty Arabica coffee is produced through collaboration between coffee chain actors from producers to end consumers. The cooperation that exists between actors forms a management system in regulating and controlling coffee quality. The system forms a governance that indirectly binds and regulates all actors. The governance analysis on the Arabica coffee value chain is carried out with the aim of knowing the type of governance formed and the actors who have the power to regulate the chain. This research data was conducted by interviewing 56 actors in the Arabica coffee value chain consisting of coffee farmers, small coffee traders, and big coffee traders. Data were analyzed using global value chain governance analysis by identifying three variables, that are complexity, codify, and capability. The results of the analysis show that the type of Arabica coffee value chain governance is a modular type with low explicit market conditions (each actor follows a stronger actor) and low power asymmetry, and the actors who have the power to regulate the value chain are consumers.